2004
DOI: 10.1016/j.jhsb.2003.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Elective Hand Surgery in Patients Taking Warfarin

Abstract: We reviewed 22 patients who had undergone either carpal tunnel decompression or release of Dupuytren's contractures while anticoagulated with warfarin. All patients continued with their usual anticoagulant regime over the period of operation, provided that the international normalized ratio (INR) was 3 or less. There was no abnormal intraoperative or postoperative bleeding in any patient. Journal of Hand Surgery (British and European volume, 2004).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 5 publications
(6 reference statements)
0
26
0
2
Order By: Relevance
“…What has become apparent, however, is that the risk of bleeding is dependent on the nature of the procedure being performed [23]. Whilst warfarin need not be discontinued for elective hand surgery, most authors conclude that major surgery can only be performed if the INR is < 1.5 [24][25][26]. About 35% of the respondents in our study would, however, consider hemiarthroplasty with an INR > 1.5 and < 2.0.…”
Section: Discussionmentioning
confidence: 70%
“…What has become apparent, however, is that the risk of bleeding is dependent on the nature of the procedure being performed [23]. Whilst warfarin need not be discontinued for elective hand surgery, most authors conclude that major surgery can only be performed if the INR is < 1.5 [24][25][26]. About 35% of the respondents in our study would, however, consider hemiarthroplasty with an INR > 1.5 and < 2.0.…”
Section: Discussionmentioning
confidence: 70%
“…Smit et al reported no complications following open carpal tunnel release (n=9) and fasciotomy for Dupuytren contractures (n=13) in patients taking warfarin. 18 A second series reported 2 hematomas that resolved with nonoperative treatment after 55 procedures (soft tissue and bony) in 39 patients on warfarin. 17 In one prospective cohort, 57 operations (49 soft tissue, 8 bony) were completed without interruption of warfarin (INR<3.0).…”
Section: Discussionmentioning
confidence: 99%
“…11,13,15 Data to support either approach are limited and relate mainly to the literature on cardiothoracic procedures (in favor of discontinuing treatment), 14 or orthopedic and ocular surgery (favoring continued treatment). [30][31][32] A 2007 audit on the United Kingdom community of vascular surgeons investigated clopidogrel use at the time of CEA and established that 52% of surgeons discontinue it preoperatively, and 51% of them administer no alternative, whereas 49% replace it with ASA. 13 No data were available on how many days before CEA the treatment was stopped.…”
Section: Discussionmentioning
confidence: 99%